Family Caregiver Reports of Their Own and Patient Symptoms in Cancer Home Hospice Approaching End-of-Life. (May 2023) - Reblin, Maija; Iacob, Eli; Tay, Djin L.; Li, Hui; Thomas Hebdon, Megan C.; Beck, Anna; Donaldson, Gary; Cloyes, Kristin G.; Ellington, Lee
Context : Family caregivers assume the primary responsibility of assessing and managing hospice cancer patient symptoms while simultaneously managing their own wellbeing and symptoms.Objectives : Describe caregivers' assessment of hospice cancer patient and their own symptoms during the last 60 days of patient life, and assess the relationship between patient and caregiver symptoms over time.Methods : Caregiver symptom report of self and cancer home hospice patient symptom data were collected via telephone in the final 60 days of patient life. Descriptive data on symptom severity and prevalence were summarized. Exploratory Factor Analysis was used to group individual symptoms. Factors representing patient symptoms, caregiver symptoms, and caregiver outlook were analyzed using mixed-effects analysis to determine relationships between factors and change in relationship between factors over time.Results : Data from 61 patient-caregiver dyads are presented. At least 1 day of moderate-to-severe symptoms were reported in the majority of dyads. Significant auto-regressive associations were found, namely previous factor scores for an individual positively predicted the next factor scores for that individual. Previous caregiver report of patient symptoms was also positively associated with the next report of caregiver symptoms; previous caregiver report of their own symptoms were negatively associated with their next report of patient symptoms. Patient and caregiver symptoms and caregiver outlook worsened over time and the relationship between patient and caregiver symptoms strengthened closer to death.Conclusion : Our findings may guide hospice care team responses to caregiver and patient symptoms to promote individual level and unit level functioning.